THE SEA OF OMAR: THE PRACTICE OF THE DOCUMENTARY AS NARRATIVE FROM THE EU AND THE OTHER IN THE VISUAL ARTS (Palíndromo, 2019)
This research analyzes the theoretical, technical and practical procedures of the production of the documentary "O mar de Omar". The short film revisits the dawn of February 27th, 2010, when Chile was rocked by one of the most devastating earthquakes in history, causing a tsunami with waves of up to ten meters, leaving hundreds dead and missing. The story is depicts the memories of Omar, a Chilean man, who for fourteen years built his house on the beach, with mate-rials brought by the sea and lost everything in the catastrophe. The article aims to reflect the implications of modernity / coloniality on globalization and some consequences on the nature and life of people living apart from capitalist systems of power. The theoretical path starts from cultural and postcolonial studies critical to modernity / coloniality and globalization, trying to understand the process of separation of man with nature and reflections that are present today in the cultures of the southern hemisphere.
Keywords: documentary; modernity/coloniality; globalization; nature